President Obama’s Humble Face: An Authentic or a Socially Desirable Posturing? A Study on Reactions to Obama’s Autobiographical Self-Disclosures - Mastropietro, Alessia; Bull, Peter; D’Errico, Francesca; Sessa, Isora; Migliorisi, Stefano; Leone, Giovanna (Frontiers in Psychology, 2022)
Referring to the mainstream studies based on the personalization’s hypothesis, which positively evaluates signals of dominance shown by leaders, the analysis of Obama’s rhetoric stays a relevant exception. His risky recall, during his political talks, of his social difficulties as a child of a mixed couple was in fact one of the more surprising aspects of his success. Nevertheless, reactions to his autobiographical sharing were scarcely explored. Based on the idea that these self-disclosures signal his responsivity toward the audience of low social condition and can, therefore, be defined as a sign of humility, this research aims to test if coherence between Obama’s words and his facial expressions of contempt, due to the seriousness of social injustices endured in his childhood, may influence the receivers’ perception of such unexpected communication. Before reading a brief autobiographical sharing taken from a “Back-to-school” speech, a highly ritualized monolog the US President addresses each year to students, 175 Italian participants were presented with a photo of Obama displaying either an expression of contempt (taken from the video of the speech) or a neutral expression. Comparisons between self-assessments of perceptions and reactions of participants assigned to the two experimental conditions show that a facial expression of contempt, coherent with words describing his school difficulties, has been crucial for perceiving this humble political discourse as authentic and not as a simple socially desirable posturing. More studies seem to be needed, however, to understand how humble speech could enhance the positive face of leaders or backfire against them.